Family caregiver's burden and the social support for older patients undergoing peritoneal dialysis. Issue 4 (20th February 2020) - Tao, Xingjuan; Chow, Susan Ka Yee; Zhang, Haifen; Huang, Jiaying; Gu, Aiping; Jin, Yan; He, Yanna; Li, Na
SUMMARY: Background: Most elderly people undergoing peritoneal dialysis (PD) treatment have a high incidence of frailty, cognitive impairment and emotional disturbance leading to a significant impact on families. The burden experienced by the family caregivers could affect their physical and emotion health. The objective of this study was to examine the level of burden on family caregivers of elderly adults receiving PD and to identify any contributing factors. Materials and Methods: This was a cross‐sectional study employing convenience sampling. Patient–caregiver dyads were recruited from the outpatient clinic of a university hospital in China in 2019. Caregivers provided information on their perceived burden and health‐related quality of life. The elderly patients reported their functional dependence and depressive symptoms in the same interview. Linear regression analyses were used to determine the factors contributing to caregivers' burden. Results: Sixty patient–caregiver dyads were recruited. The patients had a mean age of 70.7 ± 7.4 years. The caregivers reported moderate levels of burden having ZBI score of 30.5 ± 15.9. Multivariate analyses showed that being female, perceiving one's financial status as insufficient, a low level of social support for the caregiver, depressive symptoms in the patients and disability in carrying out the instrumental activities of daily life were statistically significant predictors of caregiver burden (adjusted R 2 = 0.46, p < 0.001). Conclusion: Elderly adults receiving PD who experience physical dependence and depressive symptoms are a burden for caregivers. In response to this challenge, interventions designed with the goal of supporting the emotional and mental wellbeing of caregivers are warranted.